2018
DOI: 10.1016/j.devcel.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

A Membrane Transporter Is Required for Steroid Hormone Uptake in Drosophila

Abstract: SUMMARY Steroid hormones are a group of lipophilic hormones that are believed to enter cells by simple diffusion to regulate diverse physiological processes through intracellular nuclear receptors. Here, we challenge this model in Drosophila by demonstrating that Ecdysone Importer (EcI), a membrane transporter identified from two independent genetic screens, is involved in cellular uptake of the steroid hormone ecdysone. EcI encodes an organic anion transporting polypeptide of the evolutionary conserved solute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
122
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 77 publications
(96 reference statements)
17
122
0
Order By: Relevance
“…Notably, however, a recent study challenges the dogma of freely membrane-permeable steroids (and maybe also other smaller compounds). Okamoto et al (154) have reported that in Drosophila, steroid hormones require a protein transporter for passing through cellular membranes. Moreover, once steroids become sulfated, they are trapped within the cell (5).…”
Section: Jbc Reviews: Green and Red Sulfation Pathwaysmentioning
confidence: 99%
“…Notably, however, a recent study challenges the dogma of freely membrane-permeable steroids (and maybe also other smaller compounds). Okamoto et al (154) have reported that in Drosophila, steroid hormones require a protein transporter for passing through cellular membranes. Moreover, once steroids become sulfated, they are trapped within the cell (5).…”
Section: Jbc Reviews: Green and Red Sulfation Pathwaysmentioning
confidence: 99%
“…A second paper combined results from a pooled CRISPR screen in the Perrimon lab with a more traditional in vivo approach from Naoki Yamanaka's lab at the University of California Riverside. Both groups had converged on a gene that mediates reception of a molting hormone called ecdysone 5 , but the in vivo approach involved creating and then assaying numerous RNAi-mutated flies. The CRISPR screen found the hit in an unbiased fashion and with fewer false positives to sort through and validate, says Viswanatha.…”
Section: Into the Poolmentioning
confidence: 99%
“…The classical model of diffusion-mediated steroid transport is not sufficient to explain the steroid trafficking within and across cells, and therefore specific receptormediated transport and signalling mechanisms are gaining in importance 25,26 . To date, the data regarding P5 inter-and intra-cellular transport is very limited.…”
Section: Click-proteomics Reveals P5 Interactions With Cellular Transmentioning
confidence: 99%